The Factors Influencing Students’ English Languange Acquisition at Special Needs School in Palangka Raya - Rahma, Raisha Nor; Siminto, Siminto; Qamariah, Zaitun (Jurnal Basicedu, 2024)
This study is motivated by the importance of understanding the factors that influence English language acquisition in children with intellectual disability, given that they face unique challenges in the learning process. Children with cognitive disability require customized learning methods to maximize language acquisition. This study aims to identify the factors that influence their ability to learn English. This research was conducted at SLB Negeri 1 Palangka Raya involving 7 students as research subjects. The methodology applied was a qualitative approach with data collection techniques through observation, interview, and documentation. Observation was conducted to observe students' interaction in the learning process, while interviews were conducted with educators to gain a deeper understanding of the support provided. As well as documentation related to the learning process. The results indicated that two factors were identified: external factors, such as parental support and a conducive learning environment, have a significant influence on English language acquisition. Secondly, internal factors such as learning motivation and students' cognitive capacity also play an important role in the learning process. The implications of this study emphasize the importance of developing English language teaching programs that are more inclusive and tailored to the specific needs of children with intellectual disability.